2016
DOI: 10.15252/emmm.201606623
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid catabolizing enzyme CYP26C1 is a genetic modifier in SHOX deficiency

Abstract: Mutations in the homeobox gene SHOX cause SHOX deficiency, a condition with clinical manifestations ranging from short stature without dysmorphic signs to severe mesomelic skeletal dysplasia. In rare cases, individuals with SHOX deficiency are asymptomatic. To elucidate the factors that modify disease severity/penetrance, we studied a three‐generation family with SHOX deficiency. The variant p.Phe508Cys of the retinoic acid catabolizing enzyme CYP26C1 co‐segregated with the SHOX variant p.Val161Ala in the affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 73 publications
0
21
0
2
Order By: Relevance
“…A SHOX-eltérés okozta klinikai kép súlyossága változó, az egyéb tünetet alig mutató alacsonynövéstől a csontrendszer kifejezett érintettségével járó fenotípusig. A fenotípus heterogenitására utal az a megfigyelés is, hogy az azonos mutációval rendelkező családtagok kö-zött is nagy különbség lehet a klinikai jelek megléte, illetve súlyossága tekintetében [2,3].…”
unclassified
“…A SHOX-eltérés okozta klinikai kép súlyossága változó, az egyéb tünetet alig mutató alacsonynövéstől a csontrendszer kifejezett érintettségével járó fenotípusig. A fenotípus heterogenitására utal az a megfigyelés is, hogy az azonos mutációval rendelkező családtagok kö-zött is nagy különbség lehet a klinikai jelek megléte, illetve súlyossága tekintetében [2,3].…”
unclassified
“…We have recently reported that CYP26C1 acts as a genetic modifier for SHOX deficiency [4]. Patients bearing damaging variants in both SHOX and CYP26C1 presented with more severe phenotypes when compared to family members carrying only SHOX variants.…”
Section: Discussionmentioning
confidence: 95%
“…Whole-mount in situ hybridization was performed as described previously [12]. Probes were designed and synthesized as previously described [4]. Images were taken with the microscope SZX16, Cell D Imaging Software (Olympus).…”
Section: Zebrafish Experimentsmentioning
confidence: 99%
See 2 more Smart Citations